1999
DOI: 10.1128/aem.65.10.4637-4645.1999
|View full text |Cite
|
Sign up to set email alerts
|

Toxigenic Strains of Bacillus licheniformis Related to Food Poisoning

Abstract: Toxin-producing isolates of Bacillus licheniformis were obtained from foods involved in food poisoning incidents, from raw milk, and from industrially produced baby food. The toxin detection method, based on the inhibition of boar spermatozoan motility, has been shown previously to be a sensitive assay for the emetic toxin of Bacillus cereus, cereulide. Cell extracts of the toxigenic B. licheniformis isolates inhibited sperm motility, damaged cell membrane integrity, depleted cellular ATP, and swelled the acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
1
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(121 citation statements)
references
References 25 publications
3
111
1
6
Order By: Relevance
“…In this study we show that sperm toxin produced by three food poisoning related isolates of B. licheniformis [3] was lichenysin A, known as a biosurfactant and an antibacterial agent produced by several B. licheniformis strains, BAS50, BNP29, ATCC 10716 and IM 1307 [6±10,22]. Lichenysin A is a cyclic heptalipopeptide having the sequence l-Gln, l-Leu, d-Leu, l-Val, l-Asp, d-Leu and l-Ile linked to 3-hydroxy fatty acid residue with amide (l-Gln) and lactone (l-Ile) bonds forming a cyclic structure.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In this study we show that sperm toxin produced by three food poisoning related isolates of B. licheniformis [3] was lichenysin A, known as a biosurfactant and an antibacterial agent produced by several B. licheniformis strains, BAS50, BNP29, ATCC 10716 and IM 1307 [6±10,22]. Lichenysin A is a cyclic heptalipopeptide having the sequence l-Gln, l-Leu, d-Leu, l-Val, l-Asp, d-Leu and l-Ile linked to 3-hydroxy fatty acid residue with amide (l-Gln) and lactone (l-Ile) bonds forming a cyclic structure.…”
Section: Discussionmentioning
confidence: 64%
“…The inhibition of the motility and the acrosome reaction of boar spermatozoa caused by toxins, damage to plasma membrane, swelling of mitochondria and loss of cellular ATP and NADH were analyzed as described elsewhere [3,19,21].…”
Section: Bioassaymentioning
confidence: 99%
See 1 more Smart Citation
“…To detect strains able to produce the lipopeptides, a new PCR screening approach has been developed using degenerated primers based on the intraoperon alignment of adenylation and thiolation nucleic acid domains of all enzymes implicated in the biosynthesis of each lipopeptide family (Tapi et al, 2010). All the Bacillus strains producing these lipopeptides are haemolytic, and a number of surveys have shown that about 5-6 % of Bacillus strains has the capacity to produce surfactins (From et al, 2005;Salkinoja-Salonen et al, 1999). It is know that these surfactins create pores in epithelial cells (From et al, 2007a;From et al, 2007b) and are toxic to sperm cells (Salkinoja-Salonen et al, 1999).…”
Section: Figurementioning
confidence: 99%
“…All the Bacillus strains producing these lipopeptides are haemolytic, and a number of surveys have shown that about 5-6 % of Bacillus strains has the capacity to produce surfactins (From et al, 2005;Salkinoja-Salonen et al, 1999). It is know that these surfactins create pores in epithelial cells (From et al, 2007a;From et al, 2007b) and are toxic to sperm cells (Salkinoja-Salonen et al, 1999).…”
Section: Figurementioning
confidence: 99%